2013
DOI: 10.1007/s00709-013-0525-8
|View full text |Cite
|
Sign up to set email alerts
|

Zinc ameliorates copper-induced oxidative stress in developing rice (Oryza sativa L.) seedlings

Abstract: Rice (Oryza sativa L.) seedlings were treated with different concentrations of copper (Cu) either in presence or absence of zinc (Zn), and different events were investigated to evaluate the ameliorative effect of Zn on Cu stress. In presence of high Cu concentration, growth of both root and shoots were considerably reduced. Decline in elongation and fresh mass was observed in root and shoot. Zn alone did not show any considerable difference as compared to control, but when supplemented along with high concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…5a-c), suggesting that supplemental Zn efficiently enhanced the ability of antioxidant defense, which contributed to alleviate oxidative injuries under PEG-6000 simulated drought stress. Similar reports have also shown that Zn ameliorates oxidative stress caused by excessive copper by enhancing SOD, CAT and APX activities in developing rice seedlings (Thounaojam et al 2014).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…5a-c), suggesting that supplemental Zn efficiently enhanced the ability of antioxidant defense, which contributed to alleviate oxidative injuries under PEG-6000 simulated drought stress. Similar reports have also shown that Zn ameliorates oxidative stress caused by excessive copper by enhancing SOD, CAT and APX activities in developing rice seedlings (Thounaojam et al 2014).…”
Section: Discussionmentioning
confidence: 84%
“…The AsA and GSH regeneration system is also required for the conversion of H 2 O 2 to H 2 O by APX via ascorbate-glutathione cycle (Choudhury et al 2013). Enhanced AsA and GSH contents by supplemental Zn were involved in ameliorating copperinduced oxidative stress in rice (Thounaojam et al 2014). Supplemental Zn dramatically enhanced AsA and GSH accumulations in cotton leaves under PEG-6000 simulated drought stress (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The recorded increase in total soluble carbohydrates and protein on priming with Nano ZnO was in accordance with the findings of Venkatachalam et al (2016) using Nano ZnO under Cd or Pb stress in Leucaena leucocephala seedlings and with those of Soliman et al (2015) using nano-iron and nano-zinc in salt stressed Moringa peregrina plants. This resultant increase might be due tothe involvement of Zn in the structure of various enzymes and transcriptional factors with important roles in protein and carbohydrate synthesis and regulation of nucleic acids and lipid metabolism (Bonnet et al, 2000 andThounaojam et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The ionic form of Cu 2+ caused root growth alterations in durum wheat at low concentration; 1.0 μM and high Cu concentrations (200 and 500 μM) may reduce the growth of both root and shoots (Michaud et al, 2008 andThounaojam et al, 2014). Toxicity of Cu is affected by bioavailability of metal in the soil and by the concentration of the metal as well as pH of the soil (Wang et al, 2009).…”
mentioning
confidence: 99%